Properties of the coating deposited with the diffusion of Mo&O2 oxidized powder using the APS process - Mrdak, Mihailo R. (Vojnotehnički glasnik / Military Technical Courier, 2017)
Powder Mo&O2 has an important role in the production of coatings with increased resistance to slide in conditions without the use of lubricants. Mo&O2 coatings have the low coefficient of friction and good abrasion characteristics in mechanical stresses. For the purpose of producing coatings of high hardness, Mo&O2 powder is plasma deposited with optimal parameters. The surface shape of oxide powder particles and the coating fracture surface are analysed by SEM, and the microstructure of layers is examined by light microscopy. The coating microstructure consists of Mo lamellae and MoO3 and MoO2 primary oxide thin films, which surround the Mo lamellae. The analysis of the obtained results showed that the Mo&O2 coating layers with the diffusion oxidized Mo particles have such a structure and mechanical characteristics which enable its application in working tools under the conditions of wear and sliding friction without lubricants.
Keywords: particles; friction; deposits; property; powders; oxidizers; microstructures; lubrication; Coatings